A Study Of Ergonomic Awareness Of Musculoskeletal Disorder (Msd) For Workers In Casting Line In Ceramic Factory - Hussein Md Zan; Sinatu Sadiah Shaoie; Mohd Farizal (Politeknik & Kolej Komuniti Journal of Social Sciences and Humanities, 2017)
Workers in casting line continously standing and squatting in order to move the ceramic mold. Awareness among those workers about these movements and its relation to Musculoskeletal Disorder (MSD) is still low. It is observed that those workers worked continously in the same position continuously and later they suffered discomfort on their body part. The aim of this research is to identify the perception of 55 workers in Casting Line at CeramTec Innovative Ceramic Engineering (M) Sdn. Bhd. on factors that may cause MSD. Two aspects have been identified which are the workstation and MSD symptom. The findings of this research were analyzed using SPSS (Statistical Packages for Social Science) system, version 16.0. The result shows that employees who suffer MSD are considerably high. However, there were some area that were at the average level and necesary improvements are needed to minimise the risk of MSD among the workers.